Pengaruh Struktur Modal dan Rasio Aktivitas Terhadap Profitabilitas - Jullia; Herlina Rasjid; Andi Yusniar Mendo (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to find out how much influence capital structure and activity ratios have on profitability in automotive sector companies listed on the Indonesia Stock Exchange in 2018-2022. Sample selection was carried out using purposive sampling to obtain seven companies that met the requirements as samples. The data used in this research is secondary data in the form of financial reports obtained from the Indonesia Stock Exchange (IDX) with a total of 35 financial reports observed. This research uses the statistical method of multiple linear regression in the SPSS version 26 application. The results of this research show that capital structure has a positive and significant effect on profitability, which means that every increase in capital structure by one percent will increase profitability; the activity ratio has a negative and significant effect on profitability, which means that every increase in the activity ratio will reduce profitability and; Simultaneously, capital structure and activity ratios have a positive and significant effect on profitability in automotive sector companies.